(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In these days, the money minded people use fertilizers for more more production of crops. This scnerio to make impurities of soil and the soil makes water impure by the use of fertilizers as well as pesticides. The chemical used in fertilizers and pesticides such as arsenic and mercury, which mixes in water from soil in various ways, makes it impure. The water flows from H.P. to Punjab, Haryana and then Rajasthan, gets more and more polluted due to excess use of fertilizers in these states. The water comes from the river Sutlej in these states, which is used for drinking, irrigation and all other purposes. But due to mixing of such type of dangerous chemicals in water from the impure soil from farms makes the water poluted drinkable.But, as the people are not aware of its dangerous effects and are going to drink it regularly, are affected by diseases like cancer. Our aim to mathematical modelling (statistical analysis) to show the growth rate of dangerous cancer is increasing day by dayas well as flow the water of Sutlej. We are going to understand through the graph and by the hypothetical test, is the thinking of these kind of possibilities are true or false.Statistical analysis chi- square test is most helpful test to the deep study of like to these kinds of the experiments after collecting the data and it gives most accuracy of farthest study of statistical analysis, it might give an experimental thought to precaurance of this kind of instability. It may be helpful for the human beings to understand the flowance of the water is very dangerous from the farm (irrigated and ferilized soils). It respective the water flows through the mixture of impurities is harmful to the human being in the flow of their areas and it causes the cancer higher in the respective their flowence. We are regarding this preciption and try to understand the thinking of aim is true or false by using the hypothetical tests.